Synthesis of two nitrogen-containing polyaromatic compounds through gold catalysis/DBU-promoted cyclizations - Sadaphal, Vikas Ashokrao; Wu, Tien-Lin; Liu, Rai-Shung (Chemical communications (Cambridge, England), 2024)
This work reports an efficient synthesis of novel benzo[7,8]indolizino[2,3,4,5- ija ]quinazoline derivatives between 2-(2-ethynylaryl)acetonitriles 1 and anthranils 2. The synthetic approach involves the initial formation of 7-formylindole intermediates that can be implemented by DBU to activate a novel indole-nitrile-aldehyde cyclization. This work reports novel gold catalysis and DBU-promoted cyclizations between 2-(2-ethynylaryl)acetonitriles and anthranils to construct benzo[7,8]indolizino[2,3,4,5- ija ]quinazoline frameworks.